2017
DOI: 10.1590/1678-457x.31916
|View full text |Cite
|
Sign up to set email alerts
|

Textured soy protein, collagen and maltodextrin as extenders to improve the physicochemical and sensory properties of beef burger

Abstract: Non-meat ingredients have been added as extenders to variety of meat products, such as beef burger, to improve some properties. Textured soy protein (TSP), collagen (CL) and maltodextrin (MD); and their combinations (TSPCL, TSPMD, CLMD and TSPCLMD) were added to beef burgers and then the effect on physicochemical and sensory properties was evaluated. MD and TSPMD presented higher yield and TSPMD showed lower value for the shrinkage analysis; these results showed the positive influence of the maltodextrin in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
4
15
1
Order By: Relevance
“…The major common sources of carbohydrate in the burgers produced are wheat flour and bread crumbs. The proximate composition of beef burger observed in this study was in disparity with that of Carvalho, et al [17] who reported a protein, fat, ash and carbohydrate content of 40.23, 42.50, 8.94 and 8.23% respectively in dry weight basis. This may be as a result of variation in ingredients used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The major common sources of carbohydrate in the burgers produced are wheat flour and bread crumbs. The proximate composition of beef burger observed in this study was in disparity with that of Carvalho, et al [17] who reported a protein, fat, ash and carbohydrate content of 40.23, 42.50, 8.94 and 8.23% respectively in dry weight basis. This may be as a result of variation in ingredients used.…”
Section: Discussioncontrasting
confidence: 99%
“…Texture parameters from past findings are comparable to that observed in this study. Carvalho, et al [17] reported beef burger with hardness, chewiness, cohesiveness and springiness to be 15.38, 8.23, 0.69 and 0.78 respectively while in this study these parameters were 17.51, 6.58, 0.65 and 0.57 ( Table 5). The close proximity of the values observed in this study with that of the past study could be as a resultant effect of similarity in the methods used in the preparation of the beef burgers.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Tavares et al (2007) obtained acceptation by consumers in sensorial analyses of rabbit meat burgers, suggesting that rabbit meat has potential technological use in the production of meat products. Carvalho et al (2017) did not show any improvement in sensory properties when textured soybean protein was used in processing beef burgers.…”
Section: Discussionmentioning
confidence: 78%
“…With these levels, an increase in the product's water retention has been observed (Yadav et al, 2013), improving the protein content (Londero et al, 2015) and decreasing water loss (Gök et al, 2012;Yadav et al, 2013). However, a decrease in taste and other sensory attributes in low fat meat products have been observed (Gök et al, 2012;Jalal et al, 2013;Carvalho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%